Digital Narratives of Hajj Pilgrims in the Transformation of Social Media Culture - Wibisono, Haritsyah; Hasanah, Hasyim; Jarong, Koree (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2026)
The development of digital technology has driven significant transformations in how Hajj pilgrims present their religious experiences in public spaces. This study aims to analyze forms of self-representation among Hajj pilgrims in digital narratives published on social media platforms, as well as to examine the symbolic meanings that shape the construction of their religious identities. A qualitative approach using semiotic analysis was employed to examine ten digital posts purposively selected from Instagram and TikTok. The findings indicate that pilgrims digital narratives function not only as documentation of spiritual journeys but also as performative media through which piety, social status, and religious credibility are negotiated before broader audiences. The visual and textual representations reveal a shift from collective expressions of religiosity toward consciously constructed personal practices aimed at gaining symbolic validation and public interaction. These findings contribute to the field of religious communication by highlighting digital narratives as a new arena for the production and consumption of religious identity in the era of global connectivity.